KOMUNIKASI INTERPERSONAL ANTARA DOSEN MUDA DENGAN MAHASISWA DALAM MENINGKATKAN MOTIVASI PRIBADI - nuning indah pratiwi (Universitas Pendidikan Nasional, 2017)
ABSTRACTThe concept itself is unique human character, which can be used to distinguish individual human beings from other living creatures. Humans as organisms that have evolved impetus that will cause men aware of the existence / her existence. The developments that took place later helped establish the concept of the individual concerned. Self-concept is also needed when someone does interpersonal communication with another person because of interpersonal communication is one individual communication with other individuals so get reciprocal effects that have a common meaning. Based on the above explanation, the same thing can happen inside a novice lecturer in interacting with students. Profession as a lecturer often associated with someone who has a high intellect, rarely smiling, stiff, dignified, less socializing and interacting with students outside of class hours, so students often assume that there is a gap between students and lecturers.While students are college students, mostly teenage levels of different emotions, because when individual human conduct interpersonal communication automatically psychological factors affect each character in the concept of self. The factors causing interpersonal attraction, can be distinguished from personal factors, namely the similarity of personal characteristics, emotional stress (stress), low self- esteem, solasi social and situational factors, namely physical attraction (physical attractiveness), rewards (reward), familiarity, proximity (proximity) or closeness, and the ability (competence).Keywords: Interpersonal Communication, Young Lecturer and Students, Self Motivation